Anaemia and associated factors in people living with HIV on ART in Southern Province of Zambia - Martin Chakulya; Lweendo Muchaili; Hanzooma Hatwiko; Matenge Mutalange; Memory Ngosa; Bislom C. Mweene; Geofrey Mupeta; David Chisompola; Marshall C. Mubanga; Lukundo Siame; Joreen P. Povia; Benson M. Hamooya; et al. (PLoS ONE, 2025)
Background Anaemia remains a significant comorbidity among people living with HIV (PLHIV) on antiretroviral therapy (ART) in Sub-Saharan Africa (SSA), exacerbated by biological, sociocultural, and clinical factors. Despite known sex disparities, limited data exist on sex-specific determinants of anaemia in Zambia. This study evaluates anaemia prevalence, sex differences, and associated factors among PLHIV in Southern Province, Zambia. Methods A retrospective cohort study analyzed 2,840 PLHIV aged ≥15 years from 12 districts in Southern Zambia. Data were abstracted from medical records (November–December 2024). Anaemia was defined as haemoglobin <13 g/dL (men) and <12 g/dL (non-pregnant women). Multivariable logistic regression identified factors associated with anaemia. Results Anaemia prevalence was 15.7% (446/2,840), with marked sex disparity: females exhibited 21.8% prevalence (380/1,741) versus 6.0% in males (66/1,099). Adjusted odds of anaemia were 3.24-fold higher in females (95% CI: 1.98–5.31, p < 0.0001). Widowed individuals had the highest prevalence (20.2%). Cotrimoxazole (CTX) prophylaxis reduced anaemia likelihood (14.3% vs. 18.3%, p = 0.005). Participants on INSTI-based ART had lower anaemia prevalence (11.9%) compared to protease inhibitors (26.5%) or other regimens (30.0%). Viral load was independently associated with anaemia (AOR: 1.00, p = 0.021). Advanced WHO stages (Stage 3: 50% anaemia) and lower creatinine levels correlated with increased risk. Conclusions Significant sex-based disparities in anaemia among Zambian PLHIV highlight the need for gender-responsive interventions, including nutritional support and INSTI-based ART. CTX prophylaxis demonstrates protective effects, advocating for broader integration into HIV care. Retrospective design and unmeasured confounders limit causal inference. Future research should prioritize longitudinal studies to refine anaemia management in high-burden settings.